1960
DOI: 10.1017/s0021859600021341
|View full text |Cite
|
Sign up to set email alerts
|

The value of calcium nitrate and urea for sugar beet, and the effect of late nitrogenous top dressings

Abstract: 1. Twenty-eight experiments on sugar beet in 1956–8 compared ammonium sulphate, calcium nitrate and urea applied to the seedbed before sowing. The three fertilizers were compared at rates which supplied nil, 0·6 and 1·2 cwt. N/acre. Treatments in which 0·6 cwt. N/acre was held back until the end of June were also included.2. Average responses in sugar yield were low, 0·6 cwt. N/acre provided virtually all the nitrogen required for maximum sugar production. The heavier nitrogen dressing, on the other hand, subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1961
1961
1977
1977

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…To use leaf analyses for advice on manuring of the crop, they must be made available in time for late applications of nitrogen to be given. Adams (1960) showed that nitrogen can be applied until late in June with little loss in sugar yield, but still later applications decrease both sugar percentage and total yield. Plants must therefore be analysed in early June, at the 4-to 8-leaf stage; analyses might be used to decide the dressings in subsequent years, but differences between seasons and cultivations diminish the chances of success, especially because there is a statutory interval of 3 years between beet crops on a field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To use leaf analyses for advice on manuring of the crop, they must be made available in time for late applications of nitrogen to be given. Adams (1960) showed that nitrogen can be applied until late in June with little loss in sugar yield, but still later applications decrease both sugar percentage and total yield. Plants must therefore be analysed in early June, at the 4-to 8-leaf stage; analyses might be used to decide the dressings in subsequent years, but differences between seasons and cultivations diminish the chances of success, especially because there is a statutory interval of 3 years between beet crops on a field.…”
Section: Discussionmentioning
confidence: 99%
“…2). Split dressings produced smaller concentrations early in the season and larger ones later, and such dressings may diminish sugar percentage (Adams, 1960).…”
Section: Plant Nitrate and Fertilizer Dressingmentioning
confidence: 97%
“…Widdowson, Penny & Cooke (1960) found that urea containing < 1 % biuret and ammonium sulphate gave similar yields of potatoes at rates up to 168 lb./acre of nitrogen, with no check to early growth, but that urea containing 4-5 % biuret checked early growth and gave lower yields than ammonium sulphate, especially at high rates of application. For sugar beet, Adams (1960) found that urea gave similar sugar yield's but slightly higher yields of tops than ammonium sulphate. Templeman (1961) reported that urea gave rather smaller increases in dry matter yield of grass than those from 'Nitro-chalk', while both sources gave similar average yields of wheat.…”
mentioning
confidence: 97%
“…Rate of nitrogen application = Date of harvest > > Time of nitrogen application > Interactions. 1 Authorized for publication by the Director as Journal Article No. 3620 of the Michigan Agr.…”
mentioning
confidence: 99%
“…Generally, beets have responded best to early applications of nitrogen fertilizers (5, ;2, 10). However, Adams (1) found that the sugar yield 1 was not reduced when nitrogen was applied late if some nad been applied as a preplant or at planting time. Haddock (9) noted no difference in root yield due to sidedre~sing nitrogen in midseason as compared to sidedressing iri early season.…”
mentioning
confidence: 99%